Heritage Education Actions for Knowledge and extroversion of historical and cultural heritage in Baixada Maranhense and Reentrâncias Maranhense - Marques Bandeira, Arkley (2021)
The research came from the need to provide students of the Undergraduate Program in Human Sciences - UFMA – Campus Pinheiro, heritage experiences in extraclass activities in the regions of Baixada Maranhense and Reentrâncias Maranhenses, complementing the content worked in classrooms. For that, didactic-pedagogical strategies were developed for the extroversion of the historical and cultural patrimony, with the participation of the students from the planning, through the field research and dissemination of the results. This paper will present three case studies applied in the disciplines of Brazilian Historical Heritage, Folklore and Popular Culture and History of Colonial America, whose focus was to present support of memories and stories in living laboratories, such as the Pinheiro city, Historical Center of São Luís and Alcântara and the Quilombola Community of Itamatatiua, in Alcântara